2021
DOI: 10.1007/s00380-021-01948-2
|View full text |Cite
|
Sign up to set email alerts
|

Aortic arch calcification with pericardial fat mass detected on a single chest X-ray image is closely associated with the predictive variables of future cardiovascular disease

Abstract: This study evaluated the associations between aortic arch calcification (AAC) with pericardial fat (PF) mass detected on a single chest X-ray image and predictive variables of future cardiovascular disease (CVD). The subjects were 353 patients treated with at least one of the hypertension, dyslipidemia or diabetes. All subjects were evaluated for AAC; divided into 3 groups with AAC grades of 0, 1, or 2; and examined for the presence of PF. Carotid intima-media thickness (IMT, n = 353), cardio-ankle vascular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Watanabe et al . 27 showed that the inclusion of radiographic pericardiac fat as an indicator in addition to vascular calcification improved cardiovascular risk prediction in patients with at least 1 risk factor. They argued that pericardial fat served as a marker for visceral fat, metabolic syndrome, or dyslipidemia; a greater amount of visceral fat or a greater degree of metabolic syndrome might be indicative of more severe inflammation that precipitates future cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al . 27 showed that the inclusion of radiographic pericardiac fat as an indicator in addition to vascular calcification improved cardiovascular risk prediction in patients with at least 1 risk factor. They argued that pericardial fat served as a marker for visceral fat, metabolic syndrome, or dyslipidemia; a greater amount of visceral fat or a greater degree of metabolic syndrome might be indicative of more severe inflammation that precipitates future cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The presence ( n = 141) or absence ( n = 112) of CAC on both sides was recorded using B-mode ultrasonography. Posteroanterior chest X-ray films were performed for study subjects, and AAC grade was reviewed in a manner as previously reported [ 22 , 23 ]. Subjects were divided into three groups based on the grade of AAC as follows: grade 0, no visible calcification ( n = 95, Figure 1(a) online); grade 1, small spots or a single thin area of calcification ( n = 73, Figure 1(b) online); or grade 2, one or more areas of thick calcification or circumferential calcification ( n = 83, Figures 1(c) and 1(d) ).…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were divided into three groups based on the grade of AAC as follows: grade 0, no visible calcification ( n = 95, Figure 1(a) online); grade 1, small spots or a single thin area of calcification ( n = 73, Figure 1(b) online); or grade 2, one or more areas of thick calcification or circumferential calcification ( n = 83, Figures 1(c) and 1(d) ). AAC assessment in this manner shows good accuracy and reproducibility [ 22 ]. In our study, one observer performed an AAC assessment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been reported that aortic calcification detected on CR is associated with predictive variables of future CVD, other studies have shown that LDCT is a more effective tool to detect aortic sclerosis and dissection with higher accuracy than CR in screening. [56][57][58] Moreover, recent studies have shown that aortic CT with ultra-low-dose contrast medium can also maintain high image quality as well as that of conventional dose. [59,60] These make it easier to use as a screening tool for vascular disease.…”
Section: Pulmonary Infections Screeningmentioning
confidence: 99%